Computer-Mediated Communication: A vehicle for learning - Grooms, Linda D. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2003)
The axiom of humanity’s basic need to communicate provides the impetus to explore the nature and quality of computer-mediated communication as a vehicle for learning in higher education. This exploratory study examined the experiential communication perceptions of online doctoral students during the infancy of their program. Eighty-five students were electronically queried through a 32 item open-ended questionnaire within a 13 day time frame. Preliminary findings supported the experience of Seagren and Watwood (1996) at the Lincoln Campus of the University of Nebraska, that “more information widens learning opportunities, but without interaction, learning is not enhanced” (p. 514). The overarching implications stress that faculty development and instructional planning are essential for the effective delivery of online courses, and even more so when collaborative learning is used. Facilitating group communication and interaction are areas beckoning attention as we continue to effectively organize the online classroom of this new millennium.